INCREASING ENTREPRENEURSHIP TENDENCY THROUGH CAREER SELF-EFFICACY AND CAREER MATURITY FACTORS AMONG STUDENTS - Zahrah; Baiq Dinna Widyasti; Mansurni Abadi (Jurnal Manajemen dan Bisnis Performa, 2025)
This study investigated the role of professional maturity and self-efficacy in entrepreneurship attitudes among public university student in Mataram City, West Nusa Tenggara. In Mataram, the number of educated unemployment became the second highest of unemployment in West Nusa Tenggara due to several reasons such as unavailability of a working field for graduates from university, seeking for the appropriate jobs, and preferring waiting for the opening of registration of civil servant candidates. Most of them tend to run a business, becoming an entrepreneur due to creating new jobs, solving unavailability jobs, and carrying on their passion as well as obtaining faster revenue. Job openings are undoubtedly a solution and develop the population's capacity, especially among the educated, to become a skilled workforce. But there is also a need for research related to career maturity, career interests, career readiness, and career self-efficacy to analyze problems related to links and match jobs among the educated. This study used a mixed-method; the survey samples consisted of 200 students from each public university in Mataram City, chosen at random from a stratified random sample, run used AMOS SEM. While the purposive sampling was taken to identify 20 students for the case study. This study's implications will help counsellors and universities run entrepreneurship programs and provide guidance and counselling services to help students boost their entrepreneurship tendency. Finally, developing models and modules for self-employment, adapting, and developing instruments connected to internal and external factors, and correlated with other variables that can contribute to entrepreneurship propensity.